2007
DOI: 10.1515/znc-2007-11-1207
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Effects of Saponin and Iridoid Glycosides from Verbascum pterocalycinum var. mutense Hub.-Mor.

Abstract: The anti-inflammatory and antinociceptive properties of four major compounds from the flowers of Verbascum pterocalycinum var. mutense were investigated. Saponin glycosides called ilwensisaponin A and C and iridoid glycosides known as ajugol and picroside IV were isolated from the methanolic extract. A dose-related anti-inflammatory and antinociceptive response were obtained in this study at doses of 100 and 200 mg/kg. The results of the evaluation of the anti-inflammatory activity induced by carrageenan and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…For example, flavonoids have been reported to exert antioxidant [33, 34], anti-inflammatory [35], and hepatoprotective [34, 35] activities. Moreover, saponins have been reported to exert hepatoprotective activity via modulation of its antioxidant [36] and anti-inflammatory activities [37], while condensed tannins have been suggested to possess free radical scavenging and antioxidant, anti-inflammatory and hepatoprotective activities [38]. Based on all of the reports, the MEMC-induced hepatoprotective activity is suggested to possibly involve the synergistic actions of flavonoids, saponins, and condensed tannins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, flavonoids have been reported to exert antioxidant [33, 34], anti-inflammatory [35], and hepatoprotective [34, 35] activities. Moreover, saponins have been reported to exert hepatoprotective activity via modulation of its antioxidant [36] and anti-inflammatory activities [37], while condensed tannins have been suggested to possess free radical scavenging and antioxidant, anti-inflammatory and hepatoprotective activities [38]. Based on all of the reports, the MEMC-induced hepatoprotective activity is suggested to possibly involve the synergistic actions of flavonoids, saponins, and condensed tannins.…”
Section: Discussionmentioning
confidence: 99%
“…Phenols, which were also detected in both extracts, have been shown to exert antinociceptive effect in mice in an opiod-mediated action according to a study on the extract of Emilia sonchifolia [32]. Saponins, which were also found in both extracts although in trace amounts in H. abyssinica, have also been associated with analgesic effects [33]. Some studies have also shown sterol constituents possess analgesic actions.…”
Section: Discussionmentioning
confidence: 99%
“…1.) are revealed to have effects of antioxidant [3], antinociception [4], anti-inflammation [4,5], anti-hepatitis-B virus [6], anti-myocardial ischemia [7], inhibiting multi-drug resistance of tumor [8], neuroprotective [9] and hepatoprotective [10] used clinically in the treatment of liver diseases for a long time. By improving mitochondrial function it reverses liver injuries induced by carbon tetrachloride, d-galactosamine or acetaminophen [11].…”
Section: Introductionmentioning
confidence: 99%